Digitalization of Polish illustrations for children – examples of digital archiving of paper cultural heritage - Janusz-Lorkowska, Monika (Видавництво Львівської політехніки, 2020)
The paper discusses the issue of the lack of thematically oriented digital archiving of children's books in Poland. Original works of eminent Polish illustrators are not available anymore, they can only be seen in books. Meanwhile, books published long ago cease to exist. Digitization is being undertaken by only two institutions – the Municipal Library in Lublin and a private organization from Krakow: the Polish Illustration portal for children. This work is being pursued under the slogan of Polish picturebook.
Keywords: digital library; Polish School of Illustration; digitalization of Polish illustrated book for children; Picturebook Center (OKO) at Hieronim Łopaciński Public Library in Lublin; Polish Illustration for Children in Internet